Gefitinib Represses JAK-STAT Signaling Activated by CRTC1-MAML2 Fusion in Mucoepidermoid Carcinoma Cells - Wu, Yufeng; He, Zhen; Li, Shaomei; Tang, Hong; Wang, Lili; Yang, Sen; Dong, Bing; Qin, Jianjun; Sun, Yue; Yu, Han; Zhang, Yu; Zhang, Yi; et al. (Current Cancer Drug Targets, 2019)
Background: Gefitinib is well-known as a tyrosine kinase inhibitor targeting non-smalllung- cancer (NSCLC) containing EGFR mutations. However, its effectiveness in treating mucoepidermoid carcinoma (MEC) without such EGFR mutations suggests additional targets. Objective: The CRTC1-MAML2 (C1-M2) fusion typical for MEC has been proposed to be a gefitinib target. Methods: To test this hypothesis, we developed a set of siRNAs to down-regulate C1-M2 expression. RNA-seq and Western blot techniques were applied to analyze the effects of gefitinib and siC1-M2 on the transcriptome of and the phosphorylation of tyrosine kinases in a MEC cell line H292. Results: Deep-sequencing transcriptome analysis revealed that gefitinib extensively inhibited transcription of genes in JAK-STAT and MAPK/ERK pathways. Both siC1-M2 and gefitinib inhibited the phosphorylation of multiple signaling kinases in these signaling pathways, indicating that gefitinib inhibited JAK-STAT and MAPK/ERK pathways activated by C1-M2 fusion. Moreover, gefitinib inhibition of EGFR and MAPK/ERK was more effective than that of AKT, JAK2 and STATs, and their dependence on C1-M2 could be uncoupled. Taken together, our results suggest that gefitinib simultaneously represses phosphorylation of multiple key signaling proteins which are activated in MEC, in part by C1-M2 fusion. Gefitinib-repressed kinase phosphorylation explains the transcriptional repression of genes in JAK-STAT and MAPK/ERK pathways. Conclusion: These findings provide new insights into the efficacy of gefitinib in treating mucoepidermoid carcinoma, and suggest that a combination of gefitinib and other inhibitors specifically against C1-M2 fusion could be more effective.
Keywords: Gefitinib